Effect of sex hormones on bone in primary osteoporosis - Riggs, B. Lawrence (1969)
The effect of sex hormones on bone tissue was studied in 12 osteoporotic patients. Surfaces of bone undergoing formation and resorption were determined by quantitative microradiography of iliac crest biopsy samples before and after treatment with estrogens in 11 postmenopausal women and with testosterone in one gonadally competent man. Before treatment, bone resorption was greater than normal in all but one patient and bone formation was normal. After treatment, bone resorption decreased to within the normal range in all patients, and bone formation did not change significantly. Biochemical studies showed significant decreases in serum calcium, phosphorus, and alkaline phosphatase levels and in urinary excretion of calcium and hydroxyproline. These changes are believed to be the consequence of the effect of the hormones on bone. The data indicate that the major effect of sex hormones in osteoporosis is an inhibition of bone resorption.